2023
DOI: 10.1021/acs.est.3c01342
|View full text |Cite
|
Sign up to set email alerts
|

Direct Formation of Electronic Excited NO2 Contributes to the High Yield of HONO during Photosensitized Renoxification

Abstract: Photosensitized renoxification of HNO3 is found to produce HONO in an unexpectedly high yield, which has been considered an important source for atmospheric HONO. Conventionally, the production of HONO is ascribed to the secondary photolysis of the primarily formed NO2. In this study, by using humic acid (HA) as a model environmental photosensitizer, we provide evidence of the direct formation of NO2 in its electronic excited state (NO2*) as a key intermediate during the photosensitizing renoxification of HNO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The formed RONO 2 * could then either be stabilized (pathway A) or decomposed to the alkyl radical (RO) and NO 2 (pathway B). Previous studies have reported that excited NO 2 (NO 2 *) can react with H 2 O to form both OH and HONO at wavelengths λ > 420 nm. In our study, UV light with a peak intensity at 365 nm was used, which had a shorter wavelength and a higher energy. Meanwhile, the absorption cross section of RONO 2 is larger than that of NO 2 (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formed RONO 2 * could then either be stabilized (pathway A) or decomposed to the alkyl radical (RO) and NO 2 (pathway B). Previous studies have reported that excited NO 2 (NO 2 *) can react with H 2 O to form both OH and HONO at wavelengths λ > 420 nm. In our study, UV light with a peak intensity at 365 nm was used, which had a shorter wavelength and a higher energy. Meanwhile, the absorption cross section of RONO 2 is larger than that of NO 2 (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we reasonably speculate that RONO 2 can also be excited. By analog to excited NO 2 *, the excited phenyl RONO 2 * is expected to react further with H 2 O to form a transition state that breaks the bond of H 2 O, resulting in the simultaneous generation of HONO and OH under irradiation conditions. Based on these analyses, the third reaction pathway of RONO 2 was proposed and the overall reaction was summarized as the photoexcited phenyl RONO 2 (i.e., RONO 2 *) reacting with H 2 O to form peroxide bicyclic alkoxy radical (BAR), HONO, and OH radicals (pathway C), as illustrated in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced production of HONO by an energy transfer mechanism through organic chromophores can potentially contribute to the missing budget for daytime HONO production. Furthermore, this study expands our understanding of nitrate photochemistry within single aqueous droplets, an active area of research that has recently shown some additional aspects of nitrate photochemistry including the importance of the role of excited states, and aqueous aerosol size, as well as the impact on halogen cycling for this reaction …”
mentioning
confidence: 85%
“…Gen et al used iron-organic complexes to measure increased HONO production rates . The photosensitizing effect of marine chromophoric dissolved organic matter (m-CDOM) was compared with other organic photosensitizers (humic acid and 4-benzoylbenzoic acid) by Mora Garcia et al Even more recently, Jiang et al reported that excited state NO 2 can enhance the formation of HONO in the presence of NO 3 – and humic-like substances . These studies suggested that the presence of photosensitizers increases the production rates of HONO; however, the exact mechanisms of photosensitized reactions of NO 3 – leading to the enhanced production of HONO remain unclear.…”
mentioning
confidence: 99%
“…4,96,97 Previous studies have elucidated various mechanisms associated with possible secondary reactions of NO 2 formed during photolysis, leading to increased HONO production in the presence of organic chromophoric compounds. These mechanisms encompass the reduction and photoreduction of NO 2 within humic acid films, 98 the formation of a key intermediate involving electronically excited NO 2 , followed by its interaction with coadsorbed water molecules on humic acid, 99 and so forth. Nevertheless, the DCAs cannot function as typical light-absorbing species, i.e., photosensitizers, in our experimental wavelength region.…”
Section: Roles Ofmentioning
confidence: 99%